LEARNING DIFFERENTIAL EQUATIONS: A METASYNTHESIS OF QUALITATIVE RESEARCH - Aidayatey Azman; Zaleha Ismail (Program Pascasarjana Universitas Negeri Jakarta, 2014)
Teaching methodology is continually developing over time. There is a need to revise the methods that have been planned and examined. This research explores the development of Differential Equations teaching methods from the year 2000 onwards. The methodology used in this paper is metasynthesis research. In the last chapter, the researchers proposed using online learning as a new method of teaching. Keywords: metasynthesis, Differential Equations, teaching methodology, online learning, technology.